PERCEPTION LEVEL EVALUATION OF RADIO ELECTRONIC MEANS TO A PULSE OF ELECTROMAGNETIC RADIATION - N. G. Buromenskii (Научный вестник МГТУ ГА, 2016)
The method for evaluating the perception level of electronic means to pulsed electromagnetic radiation is considered in this article. The electromagnetic wave penetration mechanism towards the elements of electronic systems and the impact on them are determined by the intensity of the radiation field on the elements of electronic systems. The impact of electromagnetic radiation pulses to the electronic systems refers to physical and analytical parameters of the relationship between exposure to pulses of electromagnetic radiation and the sample parameters of electronic systems. A physical and mathematical model of evaluating the perception level of electronic means to pulsed electromagnetic radiation is given. The developed model was based on the physics of electronics means failure which represents the description of electromagnetic, electric and thermal processes that lead to the degradation of the original structure of the apparatus elements. The conditions that lead to the total equation electronic systems functional destruction when exposed to electromagnetic radiation pulses are described. The internal characteristics of the component elements that respond to the damaging effects are considered. The ratio for the power failure is determined. A thermal breakdown temperature versus pulse duration of exposure at various power levels is obtained. The way of evaluation the reliability of electronic systems when exposed to pulses of electromagnetic radiation as a destructive factor is obtained.